Forceps deliveries and fetomaternal outcome in modern obstetrics - Okram, Sarda Devi; Betha, Kalpana; Bodhanapati, Jothsna; Tejasri, Koorapati (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: In modern obstetrics practice has witnessed an increase in the caesarean section rates everywhere. The incidence of instrumental deliveries varies between 10-12% in UK. The incidence of instrumental deliveries varies between 2.7-5% in India. There is an urgent need to reintroduce instrumental need in the modern obstetrics. Instrumental delivery is one of the basic functions of emergency care according to WHO. This study was done to know the prevalence, indications and fetal outcomes of forceps deliveries. Methods: A retrospective study was conducted at a tertiary teaching hospital, India from January 2014 to December 2018. All cephalic singleton pregnant mothers who underwent forceps delivery after 28 weeks were included. All the forceps delivery done in twins and breech vaginal delivery were excluded. Demographic data, Indication of forceps delivery, maternal complications of forceps delivery like episiotomy extension, cervical tear, vaginal wall tear, PPH and neonatal outcome like low birth weight, NICU admissions, stillbirth, APGAR score at 1 and 5 minutes were recorded. Equal number of mothers of reproductive age group 20-45 ages who underwent normal non breech vaginal deliveries were randomly selected as control. Results: The prevalence of forceps delivery was 5.25%. The most common indication was fetal distress (55%). Most of the mothers were primigravidas in age group 20-30 years (p<0.001). Regarding the neonatal outcome, 72% of the babies were having weight >2.5 kgs. APGAR <7 at 1 and 5 min was not significant. Conclusions: As fetal distress is the most common indication, every obstetrician should learn the skill of forceps delivery and it should not be a dying art.